2018
DOI: 10.1186/s40488-018-0083-x
|View full text |Cite
|
Sign up to set email alerts
|

Mean and variance of ratios of proportions from categories of a multinomial distribution

Abstract: Ratio distribution is a probability distribution representing the ratio of two random variables, each usually having a known distribution. Currently, there are results when the random variables in the ratio follow (not necessarily the same) Gaussian, Cauchy, binomial or uniform distributions. In this paper we consider a case, where the random variables in the ratio are joint binomial components of a multinomial distribution. We derived formulae for mean and variance of this ratio distribution using a simple Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…We will confine ourselves to a first-order Taylor expansion around (µ v , µ w ) to make the analytic derivation of the approximation of Var[θ k ] feasible. The same observation has been made by [25,12] and [26, p. 351] to approximate the variance for a ratio random variable. We obtain:…”
Section: A Appendix: Proofssupporting
confidence: 60%
See 1 more Smart Citation
“…We will confine ourselves to a first-order Taylor expansion around (µ v , µ w ) to make the analytic derivation of the approximation of Var[θ k ] feasible. The same observation has been made by [25,12] and [26, p. 351] to approximate the variance for a ratio random variable. We obtain:…”
Section: A Appendix: Proofssupporting
confidence: 60%
“…An elegant way to deal with a ratio of two random variables is to approximate its moments using the Taylor series following the line of reasoning of [12] and [26, p.351], since no easy analytic expression of E[θ k ] and Var[θ k ] can be derived.…”
Section: Exceptional Contexts: Evaluation and Pruningmentioning
confidence: 99%
“…Count based methods of FF determination calculate disproportion of number of reads mapped to chromosomes that differ in mother and fetus genotypes. Although they are quite reliable, they can be used only on samples with male (XX vs. XY genotype) [12] or trisomic (2 copies vs. 3 copies of an aberrant chromosome) fetuses [13,14]. In pregnancy with a healthy female fetus, the FF have to be estimated by alternative methods.…”
Section: Introductionmentioning
confidence: 99%
“…With p=(p1,p2,,p22), q1=p·u, and q2=normalp·normalv, ref. [22] showed that for sufficiently large n the following approximations of mean and standard deviation of Y holds μADA(Y)q1q2+q1q22n σADA(Y)1n(q1q2)2(1q1+1q2) where n is the total autosomal read count of a given sample (more robust approximations can be found in the paper). Observe that while the numbers q1 and …”
Section: Methodsmentioning
confidence: 99%